Effect of fire on the diversity and trophic levels of soil fauna in Hyrcanian forests after 5 years (case study: Galandroud forest) - Zeinab Ahmadi; Davoud Kartoolinejad; Mariam Molashahi; Masoumeh Shayanmehr (علوم محیطی)
Introduction: The diversity and abundance of soil fauna in the forest have an important role in nutrient cycle, and destructive factors (e.g., fire) would cause a disturbance in the balance of soil communities. In the current study, the effect of fire on biodiversity, richness, abundance, fresh biomass and trophic levels of soil-dwelling invertebrates in Galandroud forest were investigated and discussed. Material and methods: This research was conducted in districts 20 and 21 of series 11 from watershed 48 of Natural Resources and Watershed Management Department of Nowshahr. Ten 30×30 cm quadrates with 30 cm depth were randomly placed in both fired and control forests (20 quadrates in total) across two distinct using hand-sorting methods. The soils were collected into a pan, and transferred to the laboratory for identification and measuring the fresh biomass after separating the fauna into plastic bags. Then, the fresh biomass of soil animals was separately measured using a digital balance (with an accuracy of 0.0001 g) and then identified at family and order levels. The PAST software was used to calculate the dominance, biodiversity and richness indices of the soil fauna. Statistical comparisons were done with independent sample t-test using SPSS software. Moreover, the trophic levels of the soil fauna were determined and the abundance and biomass of each five main trophic groups were investigated within two fired and control forests. Results and discussion: Among the identified macrofauna, the earthworms were the most abundant. The abundance of almost all species was more in the control forests rather than the fire-burned ones, except for coleopteran beetles and the ants. The total biomass of trophic levels did not show any significant difference between the two forests, while it’s amount in the burned and control forests was 2.35 and 1.70 g.m-2,respectively. Among detritivore biomass, the biomass of earthworms and coleopteran beetles increased, while it decreased for millipedes, slaters, and Diplura in the burned forests compared to the control. According to the similar studies that have been done so far, most faunal assemblages have shown a negative response to the fire in the short term, and then their populations revived or even increased compared to the control area. Conclusion: The results revealed that almost all indices did not show a significant difference between fired and control forests after 5 years, with an exception for evenness and dominance. These findings reflect the restoration of the forest and soil fauna communities and return to the conditions before the fire. However, comparison of the faunal population at trophic levels showed that detritivores in the burned forests experienced the most reduction among all groups and damaged the most from the fire.